2018
DOI: 10.1002/jctb.5550
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of natural Yemeni zeolites as powder sorbents for ammonium valorization from domestic waste water streams using high rate activated sludge processes

Abstract: BACKGROUND In this study three natural Yemeni zeolites (NZ1, NZ2 and NZ3) having major minerals such as clinoptilolite and mordenite, were evaluated as low cost sorbents for the removal and recovery of ammonium ions. RESULTS The zeolite samples, with pHPZC = 9.1 ± 0.2, 7.9 ± 0.2 and 7.4 ± 0.2 for NZ1, NZ2 and NZ3, respectively, showed high ammonium sorption capacities. At pH 8, for treated waste waters: (i) with low NH4+ levels (from 25 to 100 mgNH4/L); and (ii) for concentrated NH4+ side streams generated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
4
2
0
Order By: Relevance
“…Comparatively, the geochemical composition of zeolite in this research were found to be comparable with previous reports (Alshameri et al, 2019;JMayai et al, 2018;Shaban and Abu Khadra, 2017). The mean ratio of SiO :Al O for representative 2 2 3 zeolite sample from the studied area is in the range of 6.34-6.98.…”
Section: Nas Al Muhammadi and A Hussin: Physical And Mineral Characterisation Of Natural Zeolitessupporting
confidence: 91%
“…Comparatively, the geochemical composition of zeolite in this research were found to be comparable with previous reports (Alshameri et al, 2019;JMayai et al, 2018;Shaban and Abu Khadra, 2017). The mean ratio of SiO :Al O for representative 2 2 3 zeolite sample from the studied area is in the range of 6.34-6.98.…”
Section: Nas Al Muhammadi and A Hussin: Physical And Mineral Characterisation Of Natural Zeolitessupporting
confidence: 91%
“…As can be seen in Table 4, the Langmuir model fits better with the experimental data, as has been found by many other authors [12,13,18] who emphasise the fact that both models fit correctly when working with low ammonium values, but for higher concentrations, only the Langmuir model allows a good fit. This is because the Freundlich model does not consider an intrinsic limit to the zeolite capacity while the Langmuir model considers that all the adsorbent material has a limited number of exchange points.…”
Section: Effect Of Zeolite Activation and Particle Sizesupporting
confidence: 81%
“…Furthermore, the procedure employed in this research based on adjusting the pH after activation by means of CO 2 stripping allows the decrease of the amount of washing water in 90% compared adjusting the pH of the zeolite by successive washings. As can be seen in Table 4, the Langmuir model fits better with the experimental d as has been found by many other authors [12,13,18] who emphasise the fact models fit correctly when working with low ammonium values, but for higher concen tions, only the Langmuir model allows a good fit. This is because the Freundlich m does not consider an intrinsic limit to the zeolite capacity while the Langmuir model siders that all the adsorbent material has a limited number of exchange points.…”
Section: Effect Of Zeolite Activation and Particle Sizesupporting
confidence: 79%
See 2 more Smart Citations